ANALISIS PELAKSANAAN RELOKASI PEDAGANG KAKI LIMA DI PASAR SIMPANG PADANG DURI KECAMATAN MANDAU KABUPATEN BENGKALIS - Ayu Ulfiani Hidayah; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The street vendors who occupy the street shoulder at Pasar Simpang Padang Duri causing traffic disruption. Implementation of the relocation of street vendors by Bengkalis Government through the Department of Market and Hygiene aims to give a decent place for the vendors and regularity of the market can be maintained. The location provided was adjusted by the number of vendors who will be relocated. However, the vendors are still reluctant to occupy a new location with a variety of reasons. This study aims to investigate the management of implementation and the factors that affect the implementation of the relocation of street vendors in Pasar Simpang Padang Duri. The concept of the theory used is the management theory propounded by G. R. Terrry consisting of planning, organizing, actuating, and controlling. This study uses descriptive qualitative research. The data collected through interviews, documentation, and observation. The results showed that the management in the implementation of the relocation of street vendors in Pasar Simpang Padang Duri have done pretty well. And the factors that affect the implementation of this relocation is budget, participation, coordination, and infrastructure. There are still some shortcomings in the implementation of this relocation, so the relocation of street vendors have not reached the goals set earlier.Keywords: management, street vendors, relocation